MODEL PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM (Studi Multisitus di Universitas Brawijaya dan Universitas Negeri Malang) - Ahmad Buchori Muslim (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2019)
Universities as autonomous educational institutions in the administration of education, made the development of this course will be submitted to the respective colleges. So that the implementation of the model of Islamic education among college one with the other universities are no exception can be different between the UB and the State University of Malang. Therefore in this study are the focus of research is; 1) how the Islamic education curriculum development at the UB and the State University of Malang; 2) how the learning system of Islamic education at the UB and the State University of Malang. This study uses qualitative approach, case study type with multi-site design, data analysis techniques in this study through the stages of data analysis of individual cases with the steps of data collection, data reduction, data presentation, and then draw a conclusion, after analysis of individual case data and then do the data analysis cross-site. These results indicate that the model of development of Islamic Religious Education conducted at UB and the State University of Malang is 1) the development of Islamic education curriculum using a competency-based curriculum, developed by learned center theme-based curriculum approach to social reconstruction. 2) learning system of Islamic education at both universities held in the classical cross-faculty and monitoring the deepening of learning outside the classroom with student active learning approach and contextual learning which leads to inquiry learning strategy. Generally that model of Islamic religious education at public universities can be categorized to a central model isolated entities / mechanisms and a decentralized model with interconnected entities / systemic organism.